Systemic and gastrointestinal candidiasis of infant mice after intragastric challenge. - Pope, L M (1979)
Systemic and gastrointestinal infection can be established in infant mice after intragastric challenge with Candida albicans. Differences in virulence of the six strains tested were noted. As early as 3 h after infection, some but not all livers, spleens, and kidneys contained C. albicans, but the peak number of colony-forming units in these organs was seen at 6 h. The early colonization of the organs could not be attributed to aspiration of the inoculum since about 90% of lungs and livers tested yielded no colony-forming units at 10 to 15 min postinfection. In animals with systemic infections, lungs, livers, kidneys, and spleens showed similar numbers of colony-forming units within the organs during the first 6 h postinfection- and then the number declined progressively up to 72 h. The gastrointestinal tract was colonized throughout a 20-day period of study. Counts made at intervals beyond day 1 yielded between 10(5) and 10(6) colony-forming units in the stomach, ileum, and cecum. Preparatory techniques for scanning electron microscopy preserved the yeast, intestinal mucus layer, and epithelial surface and made it possible to visualize the association between the pathogen and host tissues within the digestive tract.